Abstracts of oral and poster presentations given at the 10th International Workshop on Grapevine Trunk Diseases, Reims, France, 4–7 July 2017 - , (Phytopathologia Mediterranea, 2017)
The 10th International Workshop on Grapevine Trunk diseases was held in Reims, France, on July 4–7 2017. This workshop was co-organized with the COST Action FA1303 entitled “Sustainable control of grapevine trunk diseases” and supported by the International Organization of Vine and Wine (OIV). The meeting was attended by 240 participants from 29 countries and 155 papers were presented either as oral (63) or poster (92) presentations in four sessions: Pathogen characterization, Detection and epidemiology, Microbial ecology, Host-pathogen and fungus-fungus competitive interactions and Disease management. A field tour in the champagne vineyard was co-organized by the Comité Interprofessionnel du Vin de Champagne (CIVC). Delegates were presented with an overview of the Champagne region focussing on “terroir”, varietal creation and grapevine diseases, especially GTDs. The tour concluded with a visit to Mercier cellar with champagne tasting. The workshop is the 10th organized by the International Council on Grapevine Trunk Diseases (www.icgtd.org) and the 2nd one organised by the members of the COST Action FA1303 (www.managtd.eu). The next 11th IWGTD will be held in British Colombia Canada in 2019.